Improving outcomes in kidney transplantation through advances in donor organ perfusion - Hunter, James; Hosgood, Sarah; Moers, Cyril; Leuvenink, Henri; Rabelink, Ton J.; Ploeg, Rutger; Husen, Peri; Lurje, Georg (Nature reviews. Nephrology, 2025)
The global shortage of suitable donor kidneys is the primary challenge in kidney transplantation, and it is exacerbated by ageing donors with increased numbers of health issues. Improving organ assessment, preservation and conditioning could enhance organ utilization and patient outcomes. Hypothermic machine perfusion (HMP) is associated with better results than static cold storage by reducing delayed graft function and improving short-term graft survival, especially in kidneys recovered from marginal-quality donors. Although HMP is useful for organ preservation, it is difficult to assess organ viability during HMP because of the reduced metabolic activity at low temperatures, and the adoption of HMP has faced logistical challenges. The addition of oxygen during HMP is aimed at reducing ischaemia-reperfusion injury, but has shown mixed results in kidney transplantation, often depending on the duration of perfusion, although some studies found that the addition of oxygen improved outcomes in higher-risk donors. Normothermic machine perfusion helps to restore kidney function by delivering oxygen and nutrients at body temperature, potentially reducing ischaemia-reperfusion injury. Early studies suggest its safety, but clinical benefits remain unproven. Normothermic machine perfusion also holds promise for assessing organ viability pre-transplantation by enabling real-time evaluation. In this Review, we will summarize the different methods of kidney preservation, providing details of the effect that each method has on graft and patient outcomes and the strengths and limitations of each method.
COPE consortium: James Hunter, Sarah Hosgood, Cyril Moers, Henri Leuvenink, Ton J. Rabelink, Rutger Ploeg, Peri Husen, Georg Lurje [und 42 weitere]
Online verfügbar: 09. September 2025
Gesehen am 06.02.2026